2010
DOI: 10.1007/s00216-010-3945-8
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous sampling of volatile and non-volatile analytes in beer for fast fingerprinting by extractive electrospray ionization mass spectrometry

Abstract: By gently bubbling nitrogen gas through beer, an effervescent beverage, both volatile and non-volatile compounds can be simultaneously sampled in the form of aerosol. This allows for fast (within seconds) fingerprinting by extractive electrospray ionization mass spectrometry (EESI-MS) in both negative and positive ion mode, without the need for any sample pre-treatment such as degassing and dilution. Trace analytes such as volatile esters (e.g., ethyl acetate and isoamyl acetate), free fatty acids (e.g., capro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 74 publications
0
32
0
1
Order By: Relevance
“…In this paper, we focus on the application of one such approach to organic aerosol analysis, namely extractive electrospray ionisation (EESI) MS. The EESI process predominantly forms molecular ions ([M + H] + and [M − H] − ) and is able to efficiently ionise organic analytes even in complex sample matrices such as urine (Devenport et al, 2014), beer (Zhu et al, 2010) and olive oil . Doezema et al (2012) demonstrated an initial application of EESI-MS to organic aerosols, identifying a number of products formed from α-pinene ozonolysis in positive ion mode.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we focus on the application of one such approach to organic aerosol analysis, namely extractive electrospray ionisation (EESI) MS. The EESI process predominantly forms molecular ions ([M + H] + and [M − H] − ) and is able to efficiently ionise organic analytes even in complex sample matrices such as urine (Devenport et al, 2014), beer (Zhu et al, 2010) and olive oil . Doezema et al (2012) demonstrated an initial application of EESI-MS to organic aerosols, identifying a number of products formed from α-pinene ozonolysis in positive ion mode.…”
Section: Introductionmentioning
confidence: 99%
“…These assumptions were corroborated by high‐resolution mass measurements: a maximum error of 4.33 ppm between the experimental and theoretical exact masses expected for these compounds (C 6 H 12 O 2 , C 8 H 16 O 2 , C 10 H 20 O 2 and C 12 H 24 O 2 ) was noticed. Furthermore, several authors have previously reported the presence of some of these acids in fermentation processes to produce wine, beer and even rum . Finally, note that only subtle changes in the relative intensities of these anions can be observed in these mass spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Gas chromatography–flame ionization detection (GC‐FID) or gas chromatography–mass spectrometry (GC‐MS) is currently used to measure volatile compound concentrations in beer. Mass spectrometers with electron impact ionization (EI) and quadrupole or ion trap analysers are used by a number of research groups, but electrospray ionization (ESI) coupled to time‐of‐flight (ToF) mass spectrometers has also been used . Ethers, esters, acids, aldehydes, ketones, alcohols, sulfur compounds, hydrocarbon compounds, alicyclic compounds, heterocyclic compounds and aromatic compounds can be measured simultaneously using GC‐MS methods .…”
Section: Methodological Trendsmentioning
confidence: 99%